Reply—Putting a Premium on Regret - Bell, David E. (Management Science, 1985)
Anand (Anand, P. 1985. Testing regret. Management Sci. 31 114–116.) has suggested that measuring the sacrifice a person is prepared to make to avoid regret may be more difficult than I suggest in Bell (Bell, D. E. 1983. Risk premiums for decision regret. Management Sci. 29 1156–1166.). Though he believes regret is probably widespread, he is concerned that regret may be confounded with other of the psychological phenomena that I have discussed, especially disappointment (Bell [Bell, D. E. 1985. Disappointment in decision making under uncertainty. Harvard Business School Working Paper 83-18, 1982. Oper. Res. (January–February).]). I will use this opportunity for response to set my work in perspective.